The Effect of Government Expenditure on Human Resource Development and its Impact on Economic Growth: A Longitudinal Study in South Sulawesi, Indonesia - Fitrianti, A. Nur; KR, M. Yusuf Alfian Rendra Anggoro (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of government spending on human resource (HR) development and its impact on economic growth in South Sulawesi. Government spending in the education, health, and skills training sectors is the main focus of this study, which measures its effect on the Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) as indicators of HR development and economic growth. Using secondary data from the Central Statistics Agency (BPS) of South Sulawesi and government reports related to public spending, this study applies a multiple linear regression model to test the causal relationship between these variables in the period 2010-2023. The results show that government spending has a positive and significant effect on HR development, with the education sector making the largest contribution, followed by the health and skills training sectors.